THE EFFECT OF INFLATION ON ECONOMIC GROWTH IN POPULATION ON WELFARE IN INDONESIA FOR THE 2018-2022 PERIOD WITH ZIS AS A MODERATION VARIABLE - Sri Murwati Andriyani; Alfin Maulana; Erwan Aristyanto (WORLDVIEW ( Development economic and sharia studies journal ), 2023)
This study aims to analyze the effect of inflation, economic growth, population on welfare in Indonesia for the 2018-2022 period with zakat, infak, alms (ZIS) as moderation variables. This study used quantitative research using multiple regression analysis with moderated regression analysis (MRA) test. This study used secondary data in the form of monthly time series data. The data analysis technique is SEM using Partical Least Square (PLS). The result of this study is that inflation variables have a positive and significant effect on welfare in Indonesia for the 2018-2022 period. Inflation variables have a positive and significant effect on Zakat, Infaq, Alms (ZIS). Economic growth variables have a positive and significant effect on welfare in Indonesia for the 2018-2022 period. Economic growth variables have a positive and insignificant effect on Zakat, Infaq, Alms. The population variable has a positive and insignificant effect on the welfare in Indonesia for the 2018-2022 period. The population variable has a positive and insignificant effect on Zakat, Infaq, Alms (ZIS). Welfare variables in Indonesia for the 2018-2022 period on Zakat, Infaq, Alms (ZIS) are positive and significant.